Manajemen Mutu Pendidikan dalam Meningkatkan Proses Belajar Mengajar di SMP Negeri 2 Binjai - Siahaan, Amiruddin; Akmalia, Rizki; Syafriani, Yuni; Ramadhani, Suci; Ahmad, Amar Khairi; Sihombing, Hulga Ryan Shori (Lembaga Yasin AlSys, 2022)
This study aims to find out how Educational Quality Management Improves the Teaching and Learning Process at SMPN 2 BINJAI. This type of research uses qualitative research, where data collection techniques are interviews, observation, and documentation. Data analysis was carried out by presenting data, reducing data, and drawing conclusions. The results of the research reveal the following: Educational Quality Management, How to Improve the Teaching and Learning Process, How to Improve the Teaching and Learning Process. This research will contribute to school principals and teachers in improving the teaching and learning process.